2014
DOI: 10.5964/ejcop.v3i1.18
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This is the published version of the paper.This version of the publication may differ from the final published version. Permanent repository link AbstractThis grounded theory study explored the existential lived experience of migrants and second-generation Greek-Cypriot returnees to Cyprus and implications for counselling psychology. It looked at their motivation to return/migrate, their encounter with the new world and desires to belong. Eight semi-structured interviews were conducted with four migrants and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…Therefore, there is a need to introduce new tools, courses, workshops, multicultural client interaction and multimedia approaches to reshape the personality of the therapists working in a multi‐stressed environment. Similar results reported by Luca and Filipoppoulos (2014) suggested that experience in counselling psychology is important for dealing with patients under stressful conditions. However, existential transition and psychological adjustment, counselling psychology approaches, are crucial in this.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, there is a need to introduce new tools, courses, workshops, multicultural client interaction and multimedia approaches to reshape the personality of the therapists working in a multi‐stressed environment. Similar results reported by Luca and Filipoppoulos (2014) suggested that experience in counselling psychology is important for dealing with patients under stressful conditions. However, existential transition and psychological adjustment, counselling psychology approaches, are crucial in this.…”
Section: Discussionsupporting
confidence: 85%